2019
DOI: 10.1080/15459624.2019.1568444
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of disposable inhalable aerosol sampler at a copper electrorefinery

Abstract: The performance of the disposable inhalable aerosol sampler (DIAS), newly developed to be cost-effective and comparable to the inhalable particle sampling convention, was evaluated. Forty-eight sets of copper exposure measurements (23 personal and 25 area) with pairs of the DIAS prototypes and the IOM inhalable samplers were collected at an electrorefinery facility. For the combined data (personal and area), the geometric mean (GM) concentrations of copper were 36.1 μg m−3 (range of 0.8 – 337.7 μg m−3) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Only one article was identified for copper dust sampling [ 45 ]. This article compared a disposable version of the original IOM head (sampler is referred to as a disposable inhalable aerosol sampler (DIAS)) that had been developed with an IOM sampler for the inhalable fraction in a copper electro refinery at a flow rate of 2.0 L min −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one article was identified for copper dust sampling [ 45 ]. This article compared a disposable version of the original IOM head (sampler is referred to as a disposable inhalable aerosol sampler (DIAS)) that had been developed with an IOM sampler for the inhalable fraction in a copper electro refinery at a flow rate of 2.0 L min −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [ 49 ] also identified that using a customized insert in a cellulosic sampler may not be appropriate for gravimetric analysis due to changes in humidity and mass variabilities. Potential errors from the wiping process of the samplers has been highlighted by Lee et al [ 45 ] such as an inconsistent pressure being applied for wiping the cap inside and internal walls. The sampler location has been noted by Lee et al [ 35 ] as a potential issue with one sampler (CFC) moving position during the sampling process, from the opener facing a 45 degree angle to the vertical at the beginning to being observed to be pointing face outward from the body at the end of the sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, after sample collection, if the collection substrate is transported while mounted in the sampler, it is possible that particles originally deposited on the collection substrate may dislodge during transportation. Such particles can thereby contribute to deposits on the walls, as well as on the base of any cover plate or plug [19]. All particles found elsewhere than on or in the collection substrate are often loosely termed "wall deposits".…”
Section: Recognition and Inclusion Of Sampler Wall Depositsmentioning
confidence: 99%
“…Copper smelter [25] 18 Cu 21% 55% Lead ore mill [26] 9 Pb 19% 35% Solder manufacture [27] 30 Pb 29% 74% Battery production [20] 16 Pb 28% 66% Battery recycling [26] 54 Pb 29% 54% Welding [28] 10 Cr(VI) 5% 55% Plating [28] 12 Cr(VI) 12% 17% Paint spray [28] 29 Cr(VI) 7% 12% Zn foundry [20] 9 Zn 53% 62% Zn plating [20] 18 Zn 27% 91% Cast iron foundry [20] 18 Fe 22% 46% Grey iron foundry [20] 18 Fe 24% 77% Bronze foundry [29] 6 Cu, Pb, Zn 19%, 13%, 15% 45%, 17%, 21% Cuproberyllium alloying [20] 4 Cu, Be 31%, 12% 40%, 39% Solder manufacturer [30] 50 Pb 45% 77% Solder manufacturer [30] 47 Sn 56% 93% [25] 17 Cu 16% 38% Copper refinery [19] 48 Cu 18% 36% Battery production [31] 11 Pb 8% 33% Welding [31] 18 Al 3% 13% Cast iron foundry [20] 18 Fe 8% 69% Grey iron foundry [20] 18 Fe 5% 16% Bronze foundry [29] 6 Cu, Pb, Sn, Zn 0%, 0%, 0%, 3% 10%, 3%, 23%, 6%…”
Section: Maximum Wall Depositmentioning
confidence: 99%